2019
DOI: 10.1109/access.2019.2924685
|View full text |Cite
|
Sign up to set email alerts
|

Machine Learning Based Integrated Feature Selection Approach for Improved Electricity Demand Forecasting in Decentralized Energy Systems

Abstract: Improved performance electricity demand forecast can provide decentralized energy system operators, aggregators, managers, and other stakeholders with essential information for energy resource scheduling, demand response management, and energy market participation. Most previous methodologies have focused on predicting the aggregate amount of electricity demand at national or regional scale and disregarded the electricity demand for small-scale decentralized energy systems (buildings, energy communities, micro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
52
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 88 publications
(53 citation statements)
references
References 27 publications
0
52
0
1
Order By: Relevance
“…The BGA-GPR-based FS is executed for each of the four buildings. The obtained FS results are given in Table III. 2,3,4,5,6,7,8,9,12,14,16,18,19,20 As shown in Table III, the number of features selected by the devised FS method is noticeably smaller than the size of the predictor space (number of candidate variables in Table I). That means there have been insignificant and repeated information by most of the features in the original predictor space.…”
Section: Case Study and Experimental Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The BGA-GPR-based FS is executed for each of the four buildings. The obtained FS results are given in Table III. 2,3,4,5,6,7,8,9,12,14,16,18,19,20 As shown in Table III, the number of features selected by the devised FS method is noticeably smaller than the size of the predictor space (number of candidate variables in Table I). That means there have been insignificant and repeated information by most of the features in the original predictor space.…”
Section: Case Study and Experimental Resultsmentioning
confidence: 99%
“…Occupancy represents the number of heat energy users (people) in the building at each time interval. It has been found that building energy consumptions have a high correlation with their user (people) occupancies [19]. However, due to limitation of time and resources for direct measurement of occupancy at the buildings, we have used indirect representation of buildings occupancy using two additional variables, the holiday indicator and period of the day.…”
Section: Tii-19-4151mentioning
confidence: 99%
See 1 more Smart Citation
“…A day-ahead market was started in 1990, with the England & Wales Electricity Pool in the United Kingdom being one of the world's leading markets [70]; to trade in such a market, it was essential to grasp and forecast demand and to plan the operation of generators in accordance with demand. In particular, there have been many studies on the forecast of total demand on the electric power system for various forecasting time horizons [71][72][73][74] and for various applications and situations [75][76][77]. Many time-series statistical modeling methods and data-driven prediction methods have been proposed.…”
Section: Grasping and Forecasting Energy Fluctuationsmentioning
confidence: 99%
“…Using the cluster analysis method to divide 12-month data into seasonal-based data, and considering multi-input and multi-output, Bedi and Toshniwal [21] used long short-term memory (LSTM) to forecast the long-term electric load. Eseye et al [22] first used the binary genetic algorithm (BGA) to select features, then applied gaussian process regression (GPR) to evaluate the fitness function of the feature, and finally employed feedforward artificial neural network (FFANN) to predict the electric load. The annual MAPE value of the proposed method can reach 1.96%.…”
Section: Introductionmentioning
confidence: 99%